Exploring the physical, psychological and social well-being of people with rheumatoid arthritis during the coronavirus pandemic: a single-centre, longitudinal, qualitative interview study in the UK. Issue 7 (26th July 2022) - Ryan, Sarah; Campbell, Paul; Paskins, Zoe; Hider, Samantha; Manning, Fay; Rule, Katrina; Brooks, Michael; Hassell, Andrew
Abstract : Objective: Rheumatoid arthritis (RA) is an autoimmune, inflammatory, systemic condition that requires specific drug treatment to suppress disease activity and prevent joint deformity. To manage the ongoing symptoms of joint pain and fatigue patients are encouraged to engage in self-management activities. People with RA have an increased incidence of serious illness and mortality, with the potential to impact on quality of life. This study explored patients' experiences of living with RA on physical, psychological and social well-being as well as their ability to employ self-management skills during the coronavirus pandemic. Design: Qualitative, longitudinal (baseline, 16 September to 23 November 2020 and after 2–4 months, 11 January to the 17 January 2021), semistructured telephone interviews. Setting: A rheumatology service based in a community hospital. Participants: 15 adults with RA. Main outcomes: Data were analysed using interpretative phenomenological analysis. Results: Five themes were identified that related to impact on (1) fear: the dominant emotion, (2) social connections and work practices, (3) physical health, (4) identity and (5) self-management as a coping mechanism. The overriding emotion was one of fear, which remained high throughout both interviews. The negative impact on social well-being increased as the pandemic progressed. Conversely, physical health was not affected at either time point, although participants reported difficulty in interpreting whether physical symptoms were attributable to their RA or COVID-19. Recognition of increased vulnerability led to a reassessment of self-identity; however, respondents reported using previously learnt self-management techniques to cope in the context of the pandemic. Conclusions: The main impact was on emotional and social well-being. Levels of fear and vulnerability which affected self-identity remained high throughout the pandemic and the impact on social well-being increased over time. Physical health remained largely unaffected. Self-management skills were used to maintain a sense of well-being.